2018
DOI: 10.7322/jhgd.152182
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Metabolic Syndrome in Brazilian quilombola communities: A Crosssectional Study

Abstract: Introduction: The lifestyle of quilombola communities has changed due to extra community influence, thus affecting their environmental and behavioral factors related to the Metabolic Syndrome (MS). However, little is known about the influence of MS on the Quality of Life (QoL) of quilombola residents. Objective: We aimed to study the association between MS and QoL in quilombola communities in northern Tocantins, Brazil. Methods: The QoL of 147 adults from five quilombola communities from Tocantins was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…Many quilombolas were infected and recovered, but some died due to lack of health information and also because they did not receive comprehensive health care, equally and with quality in their territories [ 25 ]. This information reinforces what many studies emphasize the lack of assistance and access to health services [ 45 , 46 , 47 , 48 , 52 , 57 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Many quilombolas were infected and recovered, but some died due to lack of health information and also because they did not receive comprehensive health care, equally and with quality in their territories [ 25 ]. This information reinforces what many studies emphasize the lack of assistance and access to health services [ 45 , 46 , 47 , 48 , 52 , 57 ].…”
Section: Discussionsupporting
confidence: 86%
“…A study on quality of life and metabolic syndrome conducted with 147 adult quilombolas from the central region of the State of Tocantins found that 48% of them had SAH [ 48 ]. In this same thought, a study on arterial hypertension and related factors in quilombola communities in Vitória da Conquista-BA also found high levels of blood pressure [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the value found for the prevalence of SM, studies also carried out with quilombola populations in the north of the country found similar prevalences, 32.1% 22 and 33.3% 23 , respectively.…”
Section: Discussionmentioning
confidence: 79%
“…Studies carried out with quilombola populations show the prevalence of females [20][21][22]24,25 . Regarding selfdeclaration, it is observed that the brown and black selfdeclarations are constant in the studies, corroborating with the results found 22,24 .…”
Section: Discussionmentioning
confidence: 99%